Interdisciplinarity in Multimedia Development: Observations of the Information Media Design Group at Rutgers University - Muller, Silvia; Petroski, David John; Crosbie, Bill (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2014)
No abstract available.